2020
DOI: 10.14421/ekbis.2020.4.1.1244
|View full text |Cite
|
Sign up to set email alerts
|

Does The Banking Information System Affect Customer Satisfaction and Loyalty?

Abstract: This research examines customer satisfaction and loyalty in Islamic banking in the use of internet banking. The research was conducted based on the increase in e-banking users in Islamic banking in Indonesia. E-banking is one of the banking information system services needed today. The research method was carried out using the method of Structural Equation Modeling (SEM) through AMOS and SPSS software. Meanwhile, data collection is carried out through an online survey via a google form. The online survey found… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 26 publications
0
5
0
1
Order By: Relevance
“…Meanwhile, WebQual TM could indicate whether the ease-ofuse problem arises from problems with ease of understanding or intuitive operations. Previous studies have also indicated that higher quality of internet banking services contributes to an increase in the loyalty of Islamic banking customers (Amin, 2016;Saibil, 2020;Sathiyavany & Shivany, 2018). Thus, it is hypothesized that:…”
Section: E-banking Sevice Quality Effect On Customer Loyaltymentioning
confidence: 98%
“…Meanwhile, WebQual TM could indicate whether the ease-ofuse problem arises from problems with ease of understanding or intuitive operations. Previous studies have also indicated that higher quality of internet banking services contributes to an increase in the loyalty of Islamic banking customers (Amin, 2016;Saibil, 2020;Sathiyavany & Shivany, 2018). Thus, it is hypothesized that:…”
Section: E-banking Sevice Quality Effect On Customer Loyaltymentioning
confidence: 98%
“…Recent works regarded consumer loyalty as the ultimate goal because loyal consumers yield many benefits to a firm (Kim and Kim, 2018; Yang et al , 2013). Several studies have defined the loyalty and demonstrated the effects of antecedents on it in various contexts (Chen et al , 2014; Luarn and Lin, 2003; Mohammadi, 2015b; Saibil, 2020). The key determinants of loyalty include trust, satisfaction, emotion, perceived value and service quality (Kim, 2019; Kim and Kim, 2018; Kim et al , 2009; Ofosu-Boateng and Acquaye, 2020).…”
Section: Literature Reviewmentioning
confidence: 99%
“…In the information system (IS) and marketing domains, several researches have investigated the key antecedents that influence loyalty in various contexts (Chen et al , 2014; Gruen et al , 2006; Luarn and Lin, 2003; Russell-Bennett et al , 2007; Saibil, 2020). Satisfaction is widely regarded as an imperative predictor of loyalty (Aktepe et al , 2015; Chen et al , 2014; Gallarza et al , 2016; Ofosu-Boateng and Acquaye, 2020; Wang et al , 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Customer loyalty is an essential requirement for all companies, especially service-oriented industries such as banking. Good relationships with customers may act as an accurate indicator of a company's success (Saibil, 2020).…”
Section: Introductionmentioning
confidence: 99%